Fenomena Kelompok Sempalan Islam di Indonesia - Ahmad Choirul Rofiq (Ulumuna, 2007)
Understanding about religious splinter groups in Indonesian context is mainly identified through their theological difference from that of muslims majority. Their theological beliefs and practices are considered deviant from the majority’s “true” theology and practices. It at least can be concluded from the fatwa of MUI which then become formal reference to most muslims people in Indonesia. Though the fatwa face many critiques from some muslims groups, especially liberal muslims activists, but it remain assumed as truth by the majority of Indonesian muslims. There are many factors supporting the emergence of splinter groups in Indonesia. Beside the existence of some “advocates” such as liberal muslims activists and mass media, lack of law enforcement and the failure of religious leaders to educate their people to be more anticipative to the emergence of splinter groups. It is necessary to initiate open dialogues with followers of splinter groups, especially their leaders.